LDPC CODED MULTIUSER MC-CDMA PERFORMANCE OVERMULTIPATH RAYLEIGH FADING CHANNEL (Journal of Engineering, 2011)
This work presents the simulation of a Low density Parity Check (LDPC) coding scheme withmultiuserMulti-Carrier Code Division Multiple Access (MC-CDMA) system over Additive WhiteGaussian Noise (AWGN) channel and multipath fading channels. The decoding technique used inthe simulation was iterative decoding since it gives maximum efficiency with ten iterations.Modulation schemes that used are Phase Shift Keying (BPSK, QPSK and 16 PSK), along with theOrthogonal Frequency Division Multiplexing (OFDM). A 12 pilot carrier were used in the estimatorto compensate channel effect. The channel model used is Long Term Evolution (LTE) channel withTechnical Specification TS 25.101v2.10 and 5 MHz bandwidth including the channels of indoorto outdoor/ pedestrian channel and Vehicular channel